Effects of Artificial Turf and Natural Grass on Physical and Technical Performance of Professional Soccer Players - Ávalos Guillén, Juan Carlos (2017)
The purpose of this study was to compare the effect of artificial turf (AT) and natural grass (NG) on the physical and technical performance of professional soccer players. A total of 17 healthy male soccer players (24.0 ± 4.1 years, height 174 ± 6.1 cm; body weight 73.4 ± 6.3 kg; body fat % 14.2 ± 2.3; VO2max 55.5 ± 5.3 ml/kg/min) from a Costa Rican Professional Soccer League club were subjected to different tests in both types of surfaces (technical test, agility test, repeated sprint ability test, and a small-sided game [8 minutes, 32 x 32 meters, 5 vs. 5]). Players were monitored using a GPS in two sessions, separated by 48 hours, during the club’s pre-season. There were no significant differences between the two types of surfaces for the technical, agility, and repeated sprint ability tests. The physiological and kinematic variables analyzed during the small-sided game presented significant differences in average heart rate (NG = 168.5 ± 8.8, AT = 154.8 ± 11.8, p <.001), maximum heart rate (NG = 183.2 ± 8.3, AT = 175.9 ± 10.4, p =.02), body load (NG = 34.3 ± 11.2, AT = 30.5 ± 11.4, p =.03), and total impacts (NG = 230.1 ± 89.5, AT = 194. 8 ± 86.4, p=.03). It is concluded that playing on the natural grass surface caused more impact on physiological and perceived body load in players. In the case of technical variables, it is concluded that there were no statistically significant differences between the two types of surfaces (p <0.05).